PARTISIPASI MASYARAKAT DALAM PENGELOLAAN MANGROVE DI DESA WAIHERU KECAMATAN BAGUALA KOTA AMBON - Maros, Rio; Tjoa , Marthina; Pattimahu, Debby (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The aim of this research is to determine forms of management, forms of participation, levels of participation and factors that influence community participation in Waiheru Village, Baguala District, Ambon City. This research was conducted in Waiheru Village, Teluk Ambon District, Ambon City in July - August 2023. The method used used in this research is qualitative and quantitative research using a survey method where data is obtained by interviewing and filling in a list of questions and using a purposive sampling method (purposeful sampling) to determine a sample of village communities, the types of data taken include: data about the forms of community participation mangrove management using the concept of Preity (1995). The forms of mangrove forest management carried out by the Waiheru Village community include seeding, planting, maintenance, utilization in the form of tourist attractions. The participation of the Waiheru village community in the forms of mangrove forest management in the form of a dominant typology of participation was found, namely, passive participation, participation in information, participation by consultation, participation for material rewards (participation for material incentives), as well as functional participation, apart from the typology of participation above, there are also forms of participation in the form of skills participation, social participation and energy.